1996
DOI: 10.1006/brln.1996.0024
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Syntactic Comprehension by Positron Emission Tomography

Abstract: Positron Emission Tomography (PET) was used to determine regional cerebral blood flow (rCBF) when eight normal right-handed males read and made acceptability judgments about sentences. rCBF was greater in Broca's area (particularly in the pars opercularis) when subjects judged the semantic plausibility of syntactically more complex sentences as compared to syntactically less complex sentences. rCBF was greater in left perisylvian language areas when subjects had to decide whether sentences were semantically pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

61
407
6
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 601 publications
(477 citation statements)
references
References 43 publications
61
407
6
3
Order By: Relevance
“…In visual sentence comprehension, this result for the inferior frontal region is consistent with findings in several studies [Caplan et al, 1998;Just et al, 1996;Stromswold et al, 1996] that vary in the tasks, baselines, and sentence types, but which all reported an increase in the activation in this region with increasing complexity. The results are also consistent with an auditory study that found increases in the inferior frontal region for more complex sentences [Caplan et al, 1999].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In visual sentence comprehension, this result for the inferior frontal region is consistent with findings in several studies [Caplan et al, 1998;Just et al, 1996;Stromswold et al, 1996] that vary in the tasks, baselines, and sentence types, but which all reported an increase in the activation in this region with increasing complexity. The results are also consistent with an auditory study that found increases in the inferior frontal region for more complex sentences [Caplan et al, 1999].…”
Section: Discussionsupporting
confidence: 90%
“…Generally, comparisons across such studies have shown roughly similar areas of activation, nearly always including two cortical areas, the left inferior frontal gyrus (LIFG) and the left posterior superior and middle temporal gyri [e.g., Caplan et al, 1998Caplan et al, , 1999Just et al, 1996;Keller et al, 2001;Mazoyer et al, 1993;Schlosser et al, 1998;Stromswold et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have previously reported that a selective priming effect on syntactic decisions, but not on semantic decisions, was induced when event-related transcranial magnetic stimulation was administered to the left IFG with a specific timing . Previous neuroimaging studies have also reported syntactic complexity effects on left IFG activation in English sentences [Dapretto and Bookheimer, 1999;Stromswold et al, 1996], as well as an effect of grammatical rules contrasted with linguistically illegal rules [Musso et al, 2003] or an effect of the language-specific linearization rules for arguments [Grewe et al, 2005[Grewe et al, , 2006 as noted earlier. The present study further clarifies a specific and independent role of the left dF3t during the noncanonical processing of syntactic reanalysis.…”
Section: Discussionsupporting
confidence: 55%
“…Three regions have traditionally been identified as candidates for syntactic processing (Fedorenko et al, 2012;Friederici and Kotz, 2003;Grodzinsky and Friederici, 2006;Kaan and Swaab, 2002). Historically, Broca's area or left inferior frontal gyrus (IFG) has been most associated with syntax (Ben-Shachar et al, 2003;Ben-Shachar et al, 2004;Bornkessel-Schlesewsky et al, 2009;Caplan et al, 2008;Caplan et al, 2000;Carramazza and Zurif, 1976;Dapretto and Bookheimer, 1999;Embick et al, 2000;Friederici et al, 2006;Grodzinsky, 2001;Just et al, 1996;Santi and Grodzinsky, 2007;Stromswold et al, 1996). In addition, the left anterior temporal lobe (ATL) has often been linked to computations related to the manipulation of syntactic structure (Brennan et al,…”
Section: Introductionmentioning
confidence: 99%